# How to solve 1-x/3-3/2(2-x-5/2)+x+3/4=1

Our mission is to systematically share mathematics information to people around the world and to make it universally accessible and useful.
The solution of this question How to solve 1-x/3-3/2(2-x-5/2)+x+3/4=1 has been explained in a very simple way by a well-known teacher by doing addition, subtraction, and fractions.
For complete information on how to solve this question How to solve 1-x/3-3/2(2-x-5/2)+x+3/4=1, read and understand it carefully till the end.

Let us know how to solve this question How to solve 1-x/3-3/2(2-x-5/2)+x+3/4=1.

First write the question on the page of the notebook.

## How to solve 1-x/3-3/2(2-x-5/2)+x+3/4=1

To solve this question, we will write this question in the simplest form as follows and simplify it.

\displaystyle 1-\frac{x}{3}-\frac{3}{2}\left( {2-x-\frac{5}{2}} \right)+x+\frac{3}{4}=1

\displaystyle 1-\frac{x}{3}-\frac{3}{2}\left( {\frac{{4-2x-5}}{2}} \right)+x+\frac{3}{4}=1

\displaystyle 1-\frac{x}{3}-\frac{3}{2}\left( {\frac{{-2x-1}}{2}} \right)+x+\frac{3}{4}=1

\displaystyle 1-\frac{x}{3}-\left( {\frac{{-6x-3}}{4}} \right)+x+\frac{3}{4}=1

\displaystyle 1-\frac{x}{3}-\left( {\frac{{-(6x+3)}}{4}} \right)+x+\frac{3}{4}=1

\displaystyle \frac{{3-x}}{3}+\frac{{(6x+3)}}{4}+x+\frac{3}{4}=1

\displaystyle \frac{{3-x}}{3}+\frac{{(6x+3)}}{4}+\frac{{4x+3}}{4}=1

\displaystyle \frac{{3-x}}{3}+\frac{{6x+3+4x+3}}{4}=1

\displaystyle \frac{{3-x}}{3}+\frac{{10x+6}}{4}=1

\displaystyle \frac{{\left( {3-x} \right)\times 4}}{{3\times 4}}+\frac{{\left( {10x+6} \right)\times 3}}{{4\times 3}}=1

\displaystyle \frac{{12-4x}}{{12}}+\frac{{30x+18}}{{12}}=1

\displaystyle \frac{{12-4x+30x+18}}{{12}}=1

\displaystyle \frac{{30+26x}}{{12}}=1

\displaystyle 30+26x=1\times 12

\displaystyle 26x=12-30

\displaystyle 26x=-18

\displaystyle x=\frac{{-18}}{{26}}

\displaystyle x=-\frac{{2\times 9}}{{2\times 13}}